Intraspecific trait variation of grassland species in response to grazing depends on resource acquisition strategy. (16th May 2022) - Streit, Helena; Menezes, Luciana S.; Pillar, Valério D.; Overbeck, Gerhard E.
Abstract: Question: Grazing is an important disturbance for maintenance of structure and functioning of the plant communities in grassy ecosystems. Functional characteristics of plants, which are responsible for their response to grazing, vary at inter‐ and intraspecific levels. Here, we assessed: (1) the extent of intraspecific trait variation when compared to interspecific variability; and (2) how grazing regime affects intraspecific trait variation in leaf functional traits of species with different leaf economics strategies. Location: A multisite grazing experiment in subtropical grasslands, southern Brazil. Methods: For 30 dominant grassland plant species we measured functional traits related to resource acquisition strategy and grazing response (SLA, specific leaf area; LDMC, leaf dry matter content; LA, leaf area; and FT, leaf resistance to traction) under three grazing treatments (grazing exclusion, traditional, or deferred grazing) arranged in a randomized block design. We quantified the overall proportion of intra‐ and interspecific variation and, for each species, we tested for the grazing treatment effects on intraspecific trait variation through Bayesian analysis of variance. Results: The overall contribution of intraspecific variation was up to 37% of the total variation. For most grass species, grazing exclusion led to lower values of SLA and higher values of LA, while no effect of grazing treatments was detected on intraspecific variation of LDMC and FT. Altogether, the effect of grazing management on intraspecific trait variation was more prevalent in species presenting a conservative strategy than in species with an acquisitive strategy. Conclusion: The expression of leaf traits is variable within species, especially for those species with a conservative strategy of resource acquisition. The extent of intraspecific trait variation in response to grazing depends on the considered traits and the resource acquisition strategy of the studied species. Abstract : In a grazing experiment in subtropical grasslands in southern Brazil, we tested the effects of different grazing treatments on functional traits related to resource acquisition strategy for 30 dominant species. The effect of grazing management on intraspecific trait variation was more prevalent in species presenting a conservative strategy than in species with an acquisitive strategy.